Social Work in Schools – the Missing Link? - Erna Lučić (Društvene i Humanističke Studije, 2016)
Social work in schools is a part of the professional work primarily oriented at prevention. Given the age range of children involved, elementary and high school education provides an optimal environment for an organized social intervention within primary and secondary prevention in students’ behavior. Positive provisions in Bosnia and Herzegovina allow but do not require the employment of social workers in schools. The focus of this research is in the perceptions of the different participants in the educational and social work system in regards to necessity of the mandatory employment of the social workers in schools. The research was conducted in elementary schools and high schools, as well as in designated schools for special needs children in Bosnia and Herzegovina, and in social work institutions. Among the interviewees were the teachers and other professionals employed at schools; the research also included parents as well as the employees at social services. The interviewees recognized the importance of social work in schools. While taking into consideration different participants in the research, determining attitudes on the benefits of the mandatory social work in schools showed statistically significant differences in the arithmetic means of the each group, favoring social work professionals. Social work in schools is the missing link in a complex chain of behavioral disorder prevention in students.